Peritumoral infiltration of CD3 lymphocytes makes a difference in prostate cancer - Vještica, Milka; Trivunić-Dajko, Sandra; Babić, Božana; Jungić, Saša; Berendika, Jelena (Vojnosanitetski pregled, 2025)
Background/Aim. Prostate cancer (PC) is the second most common malignancy in men, and the fifth leading cause of cancer death. The most important prognostic parameters are tumor, node, and metastasis (TNM) status, initial prostate-specific antigen (PSA), Gleason score, and grade group. However, these parameters are insufficient for accurate prediction of the course of the disease. The aim of this study was to examine the prognostic and predictive value of CD3⁺ T lymphocyte infiltration, including the CD8⁺ T-cell subset, in PC tissue across various disease stages. Methods. A prospective cohort study included 90 newly diagnosed patients with PC, divided into three groups [30 with medium/high-risk localized disease (Group A), 30 with locally advanced disease (Group B), and 30 with metastatic disease (Group C)]. The patients were followed for 120 months (10 years). The difference in the density of CD3+ and CD8+ T lymphocytes was analyzed in the tumor tissue (TT) and at the invasive margin (IM). The influence of infiltration of CD3+ T and CD8+ T lymphocytes on progression-free survival (PFS) and overall survival (OS) in patients with PC was analyzed. Lymphocytic infiltration was quantified at the area of greatest density using an optical Leica microscope at ×200 magnification and photographed with a Leica camera. The field of view was 0.226377 mm². Lymphocytes were then manually counted with the aid of commercially available software Aperio 12.0. Correlations with clinical parameters, PFS, and OS were analyzed using receiver operating characteristic (ROC) curves, Kaplan-Meier survival analysis, and correlation coefficients. Results. High peritumoral infiltration of CD3+ lymphocytes was an independent predictor of shorter PFS and OS (log-rank p < 0.001). CD3+ IM infiltration correlated significantly with initial PSA, nadir PSA, and perineural invasion (p < 0.05), while there was no correlation with Gleason score, International Society of Urological Pathology (ISUP) grade, or age. Thresholds of CD3+ IM predictive of cancer-specific mortality [area under the curve (AUC) = 0.681, p = 0.0017], OS (AUC = 0.634, p = 0.0173), and PFS (AUC = 0.657, p = 0.0062) were identified using ROC analysis. No significant prognostic value was found for CD3+ T lymphocyte infiltration in the TT, nor for CD8⁺ T lymphocyte infiltration in either TT or at the IM. Conclusion. CD3+ T lymphocyte infiltration at IM is a significant prognostic and predictive biomarker in PC, indicating tumor aggressiveness and potential influence on treatment response. These findings support the integration of immune profiling into routine histopathological evaluation to refine risk stratification and guide personalized treatment strategies in patients with PC.